International Crises and Public Support for President Clinton: United Nations' Arms Inspection in Iraq - Brody, Richard A. (Javnost-The Public, 2000)
Since the publication of John Mueller's Wars, Presidents and Public Opinion (1973) scholars have been alert to the possibility that international crises, irrespective of the wisdom of the policies from which they arise, can increase public support for the president of the United States. Mueller based his explanation, of the so-called "rally" phenomenon, on a patriotic public reaction to threats to a nation's safety. In Assessing the President: The Media, Elite Opinion and Public Support (1991) Brody and Shapiro challenge Mueller's patriotism hypothesis. Their data suggest that rallies appear if (and only if) opposition elites do not openly and actively criticise the policies, which gave rise to the crisis. Three ingredients are necessary and sufficient to produce a rally: (1) A presidential monopoly of the interpretation of the meaning of the events and the actions required to end the crisis; (2) A silent or supportive political elite; (3) News media that abjure independent policy criticism which, instead, depend entirely upon political elites to provide policy opposition. The second and third ingredients produce the president's interpretive monopoly. Faced with but one interpretation of the events and the actions, to which they give rise, the public has no basis for withholding its support. Foreign affairs are inherently ambiguous to most of the American public and without good reason to question the wisdom of foreign policy, the benefit of the doubt goes to the president. This paper will examine the usefulness of the Brody-Shapiro hypotheses in helping us understand the media, elite and public responses to the crisis that followed Iraq's attempt to limit the United Nations' inspection of its arms production facilities in February 1998.